Production, Quality Control and Pharmacokinetic Studies of (177)Lu-EDTMP for Human Bone Pain Palliation Therapy Trials - Bahrami-Samani, Ali (Shaheed Beheshti University of Medical Sciences, 2012)
Developing new bone pain palliation agents is a mandate in handling end-stage cancer patients around the world. Possibly, Lu-177 ethylenediaminetetramethylene phosphonic acid ((177)Lu-EDTMP) is a therapeutic agent which can be widely used in bone palliation therapy. In this study, (177)Lu-EDTMP complex was prepared successfully using synthesized EDTMP ligand and (177)LuCl(3). Lu-177 chloride was obtained by thermal neutron irradiation (4 × 10(13) n.cm(-2)s(-1)) of natural Lu(2)O(3) samples. Radiochemical purity of (177)Lu-EDTMP was determined by ITLC (more than 99%). Stability studies of the final preparations in the presence of human serum were performed. The biodistribution of (177)Lu-EDTMP and (177)LuCl(3) in wild-type rats was studied by SPECT imaging. A comparative accumulation study for (177)Lu-EDTMP and (177)LuCl(3) was performed for vital organs up to 7 days. The complex was obtained in high radiochemical purity (more than 99%). The complex was stable in vitro in presence of human serum as well as final formulation. Significant bone uptake (> 70%) was observed for the radiopharmaceutical. Due to better physical properties of Lu-177 compared to Sm-153 and acceptable biodistribution results of the compound, (177)Lu-EDTMP seemed to be an interesting new candidate for clinical trials for bone pain palliation therapy.